Factors that Affect Relationships at Workplace with Supervisors: Perception of Young Female Faculty Members from Kazakhstan - Yelibay, Moldir (Nazarbayev University Graduate School of Education, 2019)
There are a lot of young females who work as faculty members. They have different workplace relationships - unique connections between individuals at an employment place. Relationships at the workplace are essential because they shape an organizational culture that influences an individual’s performance. Literature states that employers do not trust the abilities of a worker because of age and gender stereotypes. Youth is perceived unreliable and inexperienced; and females are expected to avoid competition, management, and prioritize family over work. As a result, young female academics drop out of their career pursuits. There are also studies that confirm mentorship to influence positively on relationships at the workplace, resulting in career advancement for young and female faculty members. While the topics of workplace relationships and mentorship for young and female professionals are sufficiently covered in the literature, the same topic for young women is largely ignored. Many studies were conducted in the West and little is known about the experiences of young female faculty members from Kazakhstan. This study aimed to understand how young female faculty members’ age and gender impact professional relationships career with supervisors. Additionally, the study explored how mentorship shapes relationships in the workplace. The following research questions were answered in order to fulfill the purpose of the study: (1) How young female faculty members are treated by their supervisors at a workplace? (2) How is the treatment affected by the presence of mentoring relationships between the supervisor and the employee? The qualitative interview research design was employed in the study to answer the research questions. Semi-structured interviews of ten participants were analyzed with the help of thematic coding and its interpretation. The researcher used snowball sampling in order to select participants. The findings of the study provided insights on relationships at the workplace of young female faculty members and their supervisors: ageism towards junior faculty; gender norms for young female faculty; a preferred worker. Participants who have mentoring relationships with their supervisors perceive a sense of collegiality and friendship. Non-mentored participants refer to positional status and personal bias in career advancement. The study is concluded by suggesting some recommendations for policymakers and university administration on relationships at the workplace to avoid age and gender bias and to enhance mentorship.